The Problems of Public Administration in the Sphere of Healthcare in Ukraine - Біла-Тіунова, Любов Романівна; Біла-Тіунова, Л. Р.; Била-Тиунова, Любовь Романовна; Bila-Tiunova, Liubov R.; Неугодніков, Андрій Олександрович; Неугодніков, А. О.; Неугодников, Андрей Александрович; Neuhodnikov, Andrii O.; Neugodnikov, Andrey; Даниленко, Юлія Сергіївна; Даниленко, Ю. С.; Даниленко, Юлия Сергеевна; et al. (Eurasian Exercise and Sport Science Association, 2019)
The purpose of this article is to establish the level of efficiency rise ways of public administration implementation in the sphere of healthcare in Ukraine on the basis of the international experience use; to define a unified conception of the institutional and legal basics’ management in the sphere of healthcare and to offer specific recommendations as to the introduction into legal reality of Ukraine. The methodology includes general philosophical and special methods of scientific cognition namely, the system-analysis technique, the dialectical method, the Aristotelian method and the structural-functional process as well as the range of empirical methods were used while carrying out the research. Authors came to a conclusion about a low adaptation level of a present healthcare system of Ukraine to real population needs. The formal international standards consolidation in a designated sphere does not provide the services in the sphere of healthcare with the availability and quality signs. The free access ability to the international protocols, in accordance with which the treatment should be provided, has to be in Ukrainian which will allow to simplify the procedure of specific decision making in the sphere of healthcare as well as to find mistakes which can occur in medical practice in due course. The research results are relevant for domestic lawmakers and entities which carry out the public administration in the sphere of healthcare against a background of the tendencies actualization of administrative processes democratization in Ukraine. All the results are independently obtained and original (incorrect adoptions and taxes are absent). The subject of research is examined for the first time in Ukraine and has the prospective for further development.

Метою даної статті є встановлення рівня підвищення ефективності шляхів реалізації державного управління у сфері охорони здоров'я в Україні на основі використання міжнародного досвіду; визначити єдину концепцію управління інституційно-правовими основами у сфері охорони здоров’я та запропонувати конкретні рекомендації щодо впровадження в правову реальність України. Методологія включає загальнофілософські та спеціальні методи наукового пізнання, а саме: техніку системного аналізу, діалектичний метод, арістотелівський метод та структурно-функціональний процес, а також ряд емпіричних методів, які були використані при проведенні дослідження. Автори дійшли висновку про низький рівень адаптації сучасної системи охорони здоров’я України до реальних потреб населення. Формальне закріплення міжнародних стандартів у визначеній сфері не забезпечує послуги у сфері охорони здоров'я ознаками доступності та якості. Можливість вільного доступу до міжнародних протоколів, відповідно до яких має здійснюватися лікування, має бути українською, що дозволить спростити процедуру прийняття конкретних рішень у сфері охорони здоров’я, а також знайти помилки, які можуть виникнути в медичній практиці в установленому порядку. Результати дослідження є актуальними для вітчизняних законодавців та суб’єктів державного управління у сфері охорони здоров’я на тлі актуалізації тенденцій демократизації адміністративних процесів в Україні. Усі результати отримані самостійно та є оригінальними (некоректні добірки та розрахунки відсутні). Предмет дослідження розглядається вперше в Україні та має перспективу подальшого розвитку.
Bila-Tiunova L. The Problems of Public Administration in the Sphere of Healthcare in Ukraine / L. Bila-Tiunova, A. Neugodnikov, Yu. Danylenko // International Journal of Applied Exercise Physiology. - Vol. 8(2.1). - Eurasian Exercise and Sport Science Association, 2019. - Р. 540-547.
Keywords: healthcare; public administration; financing; institutional and legal basics; international standards; охорона здоров'я; державне управління; фінансування; інституційно-правові основи; міжнародні стандарти; Research Subject Categories::LAW/JURISPRUDENCE